Long-Term Outcomes of Osteochondral Allograft with Osteogenic Protein-1 Augmentation: A Twelve-Year Follow-Up - Eric Assid; Andrew Renshaw; Mawadah Samad; Richard Tupler; Deryk Jones (Case Reports in Orthopedics)
Background. Osteochondral lesions (OCLs) can significantly impact functional status and activities of daily living. Weightbearing joints are disproportionately affected due to considerable biomechanical forces in these areas. Various biologic reconstructive procedures such as microfracture, osteochondral autograft transfer (OATS) or allograft transplantation (OCA), and matrix-induced autologous chondrocyte implantation (MACI) are utilized by surgeons to treat OCLs. The integration of osteochondral allografts can restore knee function and maintain the integrity of adjacent joint surfaces. Bone incorporation has been linked to successful outcomes following OCA. Pulse lavage and carbon dioxide have been used to remove marrow elements from the superficial, middle, and deep layers of the allograft; this has been combined with the use of various biologics such as bone marrow aspirate or whole blood to augment donor bone incorporation into the host bone. We present an innovative augmentation approach in OCA transplantation demonstrating excellent incorporation of an osteogenic protein-1 (OP-1) implant (Stryker, Kalamazoo, MI) to treat a large fresh osteoarticular allograft. Case Presentation. We present a 51-year-old male who received OCA augmented with an OP-1 implant (Stryker, Kalamazoo, MI) in 2011. Due to subsequent ACL reconstruction for two years and medial meniscal repair four years following OCA transplantation, we were able to arthroscopically evaluate graft status at short- and intermediate-term follow-ups. Positive findings were further verified with radiographic imaging and patient-reported outcome measures (PROMs). Conclusion. OP-1 implants aided in the bone incorporation of a large osteochondral allograft, restoring a high functional level in a demanding sport.